Identification and characterization of CYPs induced in the Drosophila antenna by exposure to a plant odorant. - Baldwin, S.R.; Mohapatra, P.; Nagalla, M.; Sindvani, R.; Amaya, D.; Dickson, H.A.; Menuz, K. (Scientific reports, 2021)
Members of the cytochrome p450 (CYP) enzyme family are abundantly expressed in insect olfactory tissues, where they are thought to act as Odorant Degrading Enzymes (ODEs). However, their contribution to olfactory signaling in vivo is poorly understood. This is due in part to the challenge of identifying which of the dozens of antennal-expressed CYPs might inactivate a given odorant. Here, we tested a high-throughput deorphanization strategy in Drosophila to identify CYPs that are transcriptionally induced by exposure to odorants. We discovered three CYPs selectively upregulated by geranyl acetate using transcriptional profiling. Although these CYPs are broadly expressed in the antenna in non-neuronal cells, electrophysiological recordings from CYP mutants did not reveal any changes in olfactory neuron responses to this odorant. Neurons were desensitized by pre-exposing flies to the odorant, but this effect was similar in CYP mutants. Together, our data suggest that the induction of a CYP gene by an odorant does not necessarily indicate a role for that CYP in neuronal responses to that odorant. We go on to show that some CYPs have highly restricted expression patterns in the antenna, and suggest that such CYPs may be useful candidates for further studies on olfactory CYP function.